In Vitro Antibacterial Experiment of Fuzheng Jiedu Huayu Decoction Against Multidrug-Resistant Pseudomonas aeruginosa - Xu, Hongri; Liu, Chang; Li, Meng; Wang, Chengxiang; Liu, Guoxing; Wang, Honghong; Ma, Jie; Li, Lei; Chen, Meng; Cheng, Miao; Yao, Xingwei; Lin, Ying; et al. (Frontiers in Pharmacology, 2020)
Objective: Drawing a growth curve of multidrug-resistant Pseudomonas aeruginosa (MDR-PA) provides a foundation for susceptibility testing. By observing in vitro antibacterial activity and ultrastructure changes on MDR-PA of the effective components in the drug-containing serum of rats after the administration of Fuzheng Jiedu Huayu decoction (FJHD), we evaluated the inhibition and direct destruction effect of bacteria by TCM alone or combined with antibiotics. Methods: The absorbance values of MDR-PA were determined at different detection time points, and a growth curve was drawn. After gavage with FJHD, drug-containing serum was collected from the rats. Using Imipenem/ cilastatin sodium as the positive drug control, the in vitro antibacterial potency of FJHD and its drug-containing serum alone or in combination with antibiotics against MDR-PA was observed. The ultrastructural changes of MDR-PA treated by FJHD combined with antibiotics were observed by transmission electron microscopy. Results: Growth of the experimental strain manifested a lag phase in the first 1–4 h, an exponential growth phase at 5–20 h, and a plateau phase after 20 h. The best detection time during the susceptibility test was 16–20 h. The minimum inhibitory concentration (MIC) value of the FJHD extract group was 0.2 g/mL. The MIC value of the pure Imipenem/ cilastatin sodium group was 16 μg/mL. The MIC values of Imipenem/ cilastatin sodium + blank serum, 0.5-, 1-, and 2-fold drug-containing serum groups were all 16 μg/mL. The MIC values of Imipenem/ cilastatin sodium + 4- and 8-fold drug-containing serum groups were both 8 μg/mL. By observation under a transmission electron microscope, Imipenem/ cilastatin sodium + 0.5-, 1-, and 2-fold drug-containing serum groups showed bacterial structural damage. The degree of bacterial destruction was more obvious and the quantity of damaged bacteria was increased in the Imipenem/ cilastatin sodium + 4- and 8-fold drug-containing serum groups. Conclusion: Drawing the growth curve of the experimental strain had high application value for ensuring the accuracy of the drug sensitivity test results. TCM combined with antibiotics could enhance the antibacterial and direct destruction effect of bacteria in vitro, thereby inhibiting bacterial resistance to a certain extent.